Konsep Hurriyah Al-Insan dan Implikasinya Terhadap Perkembangan Kehidupan Sosial - Sugeng Wanto (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This article seeks to discuss the crisis faced by the Islamic community and its inclination towards fatalism. Various factors, such as Western hegemony and a conservative mindset among certain Muslims, have contributed to the decline of Islam. The concept of unrestricted freedom, known as free will, is being advocated as a solution. The researcher employed a mixed method approach, combining quantitative and qualitative data, to obtain a comprehensive understanding of the subject. The research findings demonstrate a positive aspect, wherein individuals possess a dynamic and optimistic outlook towards the future. Humans are expected to adapt to the evolving environment, which necessitates change. To prevent fatalism, the concept of human freedom, referred to as hurriyah al-insan, is proposed as a viable option for the Muslim community.